Properties of the feline tumour suppressor reduced expression in immortalized cells (REIC/Dkk‐3). (29th June 2016) - Ochiai, K.; Oda, H.; Shono, S.; Kato, Y.; Sugihara, S.; Nakazawa, S.; Azakami, D.; Michishita, M.; Onozawa, E.; Bonkobara, M.; Sako, T.; Shun‐Ai, L.; et al.
Abstract: Reduced expression in immortalized cells (REIC/Dkk‐3), a member of the human Dickkopf (Dkk) family, is a growth suppressor in human and canine mammary tumours. Mammary gland tumours are common neoplasms with high malignancy in female cats. The purpose of this study was to clone the feline REIC/Dkk‐3 homolog, investigate its expression in cell lines established from feline mammary gland tumours, and test its tumour suppressor function. Western blot analysis revealed that expression of the REIC/Dkk‐3 protein was reduced in feline mammary carcinoma cell lines. Forced expression of REIC/Dkk‐3 induced apoptosis in feline mammary tumour cell lines. These results demonstrate that REIC/Dkk‐3 expression, which is downregulated in feline mammary tumour cell lines, results in the induction of apoptosis in these cells. Our findings suggest that feline REIC/Dkk‐3 represents a potential molecular target for the development of therapies against feline mammary cancers.